Penguatan Karakter Tanggung Jawab Murid dalam Pembelajaran PAI melalui Keteladanan Guru dan Pendekatan Konstruktivisme - Dzulfiqar, Achmad Saifu; Choiriyah, Lailatul; Kamandhani, Rayhan Putra; Hunaida, Wiwin Luqna (Universitas Muhammadiyah Magelang, 2026)
The global developments of the 21st century, marked by digital transformation and moral crisis, demand the strengthening of character education, particularly responsibility, in Islamic Religious Education (IRE) learning. This study aims to analyse the role of teacher exemplification in strengthening students' character of responsibility through a constructivist approach in IRE learning in Indonesia.. The study employed a narrative review 20 design to critically and integratively synthesize empirical studies published between 2021 and 2025, sourced from Sinta, Scopus, DOAJ, and Google Scholar databases. Literature selection was conducted through systematic identification, screening, and eligibility evaluation based on predefined inclusion and exclusion criteria. Data were analyzed using thematic extraction, conceptual comparison, and argumentative synthesis to identify dominant patterns and research gaps. The findings indicate that teacher role modeling functions as a central pedagogical instrument in internalizing responsibility through habituation, meaningful social interaction, and contextual learning experiences. The constructivist approach enhances this process by promoting active participation, reflective engagement, and value-based meaning construction. The integration of role modeling and social constructivism produces a more transformative character education process compared to normative instructional practices. Theoretically, this study proposes an integrative conceptual model linking teacher role modeling and social constructivism in Islamic character education. Practically, it provides a contextual framework for designing value-oriented IRE instruction that effectively fosters students’ responsibility character.